A Scoping Review of the Evidence for Teaching Ultrasound-Guided Regional Anesthesia. Issue 6 (1st November 2013) - Nix, Catherine M.; Margarido, Clarita B.; Awad, Imad T.; Avila, Arsenio; Cheung, Jeffrey J.H.; Dubrowski, Adam; McCartney, Colin J.L.
Abstract : Abstract: A scoping review was performed to assess published evidence regarding how best to teach ultrasound-guided regional anesthesia (UGRA). The literature search yielded 205 articles, of which 35 met the inclusion criteria. Current literature on the topic can be divided into 3 main themes: the development of motor skills, learning and teaching sonoanatomy, and understanding of the requirements for establishing a UGRA education program and evaluation. We discuss the current status and future direction of research on UGRA training.